BOOSTING FLUORIDE-TOOTHPASTES WITH NON-FLUORIDE AGENTS FOR CARIES CONTROL - Sampaio, Caio [UNESP]; Hosida, Thayse Yumi [UNESP]; Monteiro, Douglas Roberto [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Pessan, Juliano Pelim [UNESP] (Int Soc Fluoride Research, 2023)
The widespread use of toothpastes and the limited effect of fluoride (F) on caries control have stimulated the search for agents to enhance the anticaries effect of F-containing toothpastes. The association of F and different compounds, especially calcium/phosphate-based technologies, has been extensively studied as intraoral calcium and phosphate ions play a key role on the dynamics of tooth demineralization-remineralization. Technologies include the use of organic calcium/phosphate salts, inorganic cyclophosphates, nano-hydroxyapatite, and polyols. Although promising, the predominant in vitro design of the studies emphasizes the need for clinical trials to attest the efficacy and safety of F-toothpastes associated with these technologies.
Keywords: Boosting fluoride-toothpastes; Calcium/phosphate-based technologies; Caries control; Cyclophosphates; Nano-hydroxyapatite; Non-fluoride agents; Polyols